TV Series Narration of Free Will and Activism of Human Agency Case Study; »Could Happen to You« Series - Mahdi Montazer Ghaem; Zohre Alikhani (Taḥqīqāt-i Farhangī-i Īrān)
Considering perennial relation of the masses with concepts of determinism and free will, the intrinsic importance of these concepts in the area of religion, as well as regarding the ability of media in constructing the masses’ narrative of existence and also taking into account relations between religion, state and television in Iran, this study seeks to answer the question raised in the sample case study of a religious serial concerning representation of free will to its audiences. Hence, a brief introduction of the concept in Islamic thought and its implications has offered at first, to recognize the implied conflict between absolute determinism and absolute discretion in the practical part of this research. Adopting representational theory approach, we have used a combination of discourse analysis approaches and Greimas actantial model to analyze the serial dialogs about free will and underlying structure of activism, respectively. In this study we have shown that the series inspires deterministic-oriented discourse, by drawing actors’ charts of opening and final sequences as well as their schematic diagram. Type of narrative sequences and activity pattern also are deterministic, and the series is based on retributive nature of difficulties and reward-oriented character of pleasures. Two signifiers of fatalism and dreamful are attracted in its discourse area and influencing of social structures is rejected.